Gendering spaces in European towns, 1500-1914
1 online resource.
Keywords: "Towns are imagined, lived and experienced, as much as they are conceived and constructed. They reflect cultural and intellectual currents, prevailing economic climates and unresolved tensions. They are physical entities, shaped by topography, time and technology, as well as social and spatial constructs. They are also always gendered and contested spaces. This volume, the last from the Gender in the European Town (GENETON) project, approaches life in the European town over time and across class and national boundaries. Through contextualized case studies, it provides scholars and students with new research--snapshots--of contemporary physical and built environments that explores how contemporary urban residents experienced and deployed gendered urban spaces over an important period of modernization"--